Characterization and dissolution studies of salicylic acid loaded multi-walled carbon Nanotubes / Mohd Lokman Ibrahim - Ibrahim, Mohd Lokman (Faculty of Applied Sciences, 2019)
Multi-walled carbon nanotubes (MWCNTs) have been known as an innovative carrier for drug support and delivery applications. Herein, the modification of MWCNTs was carried out to improve dispersibility and biocompatibility levels. MWCNTs were functionalized by an aqua regia of concentrated nitric acid (HNO3) and sulfuric acid (H2SO4) to produce functionalized MWCNTs (f-MWCNTs). Meanwhile, the salicylic acid was loaded on the f-MWCNTs by sonication technique and the resultant was coded as SA-MWCNTs. Dissolution analysis was carried out in the different medium of simulated body fluid (SBF), simulated gastric fluid (SIF) and simulated gastric fluid (SGF) to evaluate the profile of drug release of SA-MWCNTs. It was found that the release profile of aspirin displayed 2-stage of releases; (1) fast release within 1 to 5-hours followed by (2) sustainable release for up to 12-hours. Thus, showing the compatibility of the f-MWCNTs for salicylic acid controlled released system.